1993
DOI: 10.1111/j.1532-5415.1993.tb06175.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening Elders for Risk of Hospital Admission

Abstract: Eight easily ascertained risk factors affect elders' probability of being hospitalized repeatedly within four years. In the future, brief surveys about the presence of these factors could be used to estimate elders' risk of future hospitalization and, thereby, to identify some of those who may derive the greatest benefit from interventions designed to avert the need for hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
277
1
45

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(355 citation statements)
references
References 16 publications
(33 reference statements)
22
277
1
45
Order By: Relevance
“…Nonetheless, the following strata were statistically signifi cant: low risk (PRA<0.30), medium risk (PRA=0.30-0.49) and high risk (PRA≥0.500). 1,11,19 The observed predictive accuracy of the area under the ROC curve was 0. In our study, the PRA showed improved ability to identify elderly at risk of hospitalization within six months, when a cutoff value of 0.4 was used to defi ne the high risk population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the following strata were statistically signifi cant: low risk (PRA<0.30), medium risk (PRA=0.30-0.49) and high risk (PRA≥0.500). 1,11,19 The observed predictive accuracy of the area under the ROC curve was 0. In our study, the PRA showed improved ability to identify elderly at risk of hospitalization within six months, when a cutoff value of 0.4 was used to defi ne the high risk population.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, Boult et al 1 developed a Probability of Repeated Hospital Admissions (Predição de Risco de Admissão Hospitalar -PRA) questionnaire. 1,3,12,13 In accordance with the presence or not of risk factors, the logistic regression model applied to PRA generates a value from 0 to 1. Higher values correspond to increased risk of hospital admittance.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are close to those variables found in other studies on the general population and on elderly people. For instance, "Probability of Repeated Admission" (Pra) and "The Community Assessment Risk Screen" (CARS) tools (Boult et al, 1993;Shelton et al, 2000) include as relevant variables diagnosis of different chronic conditions (such as diabetes or heart diseases), as well as previous use of hospital resources (admissions or ED visits).…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Functional decline is associated with social isolation, reduced quality of life, and death. 3,5,7,8,14,[18][19][20][21][22] It is also an important predictor of hospitalization, 23,24 prolonged hospital stay, 25 repeat ED visits, 7,26 and the need for home care 25 . Moreover, functional decline is the most important predictor of admission to institutions and of disproportionate use of health services by the elderly population.…”
Section: Introductionmentioning
confidence: 99%